Doped nano oxide material and preparation method and application thereof
By growing cerium-doped cobalt tetraoxide particles on the foam nickel, doped nanooxide materials with a two-dimensional network structure are formed, the problem of low oxygen precipitation reaction efficiency in electrocatalytic water decomposition is solved, lower overpotential and better catalytic performance are achieved, and material costs are reduced.
Patent Information
- Application Number
- CN202510003725.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-28
AI Technical Summary
In the existing electrocatalytic water decomposition technology, oxygen precipitation reaction (OER) involves a complex four-electron transfer process, resulting in a large overpotential and limiting the electrochemical efficiency. Efficient and inexpensive catalysts are difficult to develop.
Using doped nanooxide materials, a catalyst with a two-dimensional network structure is formed by growing cerium-doped cobalt tetroxide particles on the pores and surfaces of nickel foam. The material is prepared by hydrothermal reaction and firing methods, using transition metal oxides to replace noble metal oxides, reducing costs and improving electrical conductivity.
A lower overpotential is achieved, and better catalytic performance is shown for electrocatalytic oxygen production. The catalytic process is stable and efficient, reducing material costs.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of nanomaterial catalysts, and in particular to a doped nano-oxide material and a preparation method and application thereof. Background Art
[0002] Since the Industrial Revolution, fossil energy such as oil, coal, and natural gas have been widely used. However, with the growth of the world's population and the depletion of fossil energy, global energy problems have become increasingly prominent. Therefore, it is very important to develop efficient, clean, sustainable and renewable alternative energy to fossil fuels. In recent years, the conversion and storage technologies of various types of clean energy have received widespread attention.
[0003] Currently, electrocatalytic water splitting has become one of the most promising methods to simultaneously alleviate both energy and environmental issues. However, as a step in the electrolytic water splitting reaction, the oxygen evolution reaction (OER) involves a complex four-electron transfer process, which leads to a considerable overpotential and limits the efficiency of electrochemistry. IrO2 and RuO2 have been considered to be efficient OER electrocatalysts, but their scarcity and high price limit their widespread application. Therefore, the development of a new type of efficient and inexpensive catalyst becomes very critical and challenging. Summary of the invention
[0004] The invention provides a doped nano oxide material and a preparation method and application thereof, so as to solve the technical problem of low electrochemical efficiency of water electrolysis reaction in the prior art.
[0005] To achieve the above object, the technical solution provided by the present invention is as follows: In a first aspect of the present invention, a doped nano-oxide material is provided, wherein the structure of the doped nano-oxide material is that second metal oxide particles doped with a first metal are grown in the pores and surface of nickel foam, the first metal is selected from one or more of cerium, lanthanum, gadolinium, and erbium, and the second metal is selected from one or more of cobalt, nickel, and iron.
[0006] Furthermore, the structure of the doped nano-oxide material is a two-dimensional network structure.
[0007] Furthermore, the first metal is cerium, the second metal is cobalt, and the oxide of the second metal is cobalt tetroxide.
[0008] Furthermore, the pore size of the doped nano-oxide material is 10nm to 100nm, and the specific surface area is 50m 2 / g~150m 2 / g.
[0009] The second aspect of the present invention provides a method for preparing the above-mentioned doped nano-oxide material, comprising the following steps: Dissolving a precursor of a first metal and a precursor of a second metal in a first solvent to obtain a first solution; dissolving the organic ligand in a second solvent, and adding an alkali solution to obtain a second solution; The first solution and the second solution are mixed, and nickel foam is added to obtain a third solution; After subjecting the third solution to a hydrothermal reaction, a solid phase precursor is obtained by separation; The doped nano-oxide material is obtained by firing the solid-phase precursor.
[0010] Furthermore, the organic ligand is selected from one or more of terephthalic acid, trimellitic acid, and 4,4'-biphenyldicarboxylic acid.
[0011] Furthermore, the molar ratio of the first metal to the second metal in the first solution is 1:20-100.
[0012] Furthermore, the molar ratio of the organic ligand to the solute in the alkali solution is 1:1-5.
[0013] Furthermore, the ratio of the total weight of the first metal and the second metal to the weight of the nickel foam is 1-2:1.
[0014] Furthermore, the ratio of the total weight of the first metal and the second metal to the weight of the organic ligand is 1:1.
[0015] Furthermore, the precursor of the first metal is selected from one or more of the nitrate, chloride and sulfate of the first metal; the precursor of the second metal is selected from one or more of the nitrate, chloride and sulfate of the second metal.
[0016] Furthermore, the first solvent is selected from one or more of N,N-dimethylformamide and water.
[0017] Furthermore, the second solvent is selected from one or more of N,N-dimethylformamide and water.
[0018] Furthermore, the temperature of the hydrothermal reaction is 90° C. to 110° C., and the time is 14 h to 16 h.
[0019] Furthermore, the firing temperature is 390° C. to 410° C., the heating rate is 1° C. / min to 3° C. / min, and the firing time is 5 h to 7 h.
[0020] The third aspect of the present invention provides the use of the above-mentioned doped nano-oxide material or the doped nano-oxide material prepared by the above-mentioned preparation method in electrolyzed water.
[0021] The doped nano oxide material provided by the present invention has a structure in which nano oxide particles are grown on the pores and surface of nickel foam, and the nano oxide particles are second metal oxide particles doped with a first metal. The doped nano oxide material uses transition metal oxides instead of commonly used noble metal oxides, thereby reducing material costs; moreover, the material has a lower overpotential, exhibits better catalytic performance for electrocatalytic oxygen production, and the catalytic process is stable and efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 XRD diagram of nickel foam loaded with MOF precursor in Examples 1 to 3 and Comparative Example 1 of the present invention; Figure 2 XRD diagrams of the doped nano-oxide materials of Examples 1 to 3 of the present invention and the cobalt oxide catalyst of Comparative Example 1; Figure 3 This is a SEM image of the MOF precursor grown in situ on nickel foam in Comparative Example 1 of the present invention; Figure 4 This is a SEM image of the in-situ growth of a cerium-doped MOF precursor on nickel foam in Example 2 of the present invention; Figure 5 This is a SEM image of the cobalt tetraoxide catalyst in Comparative Example 1 of the present invention; Figure 6 This is a SEM image of the doped nano-oxide material in Example 2 of the present invention; Figure 7 This is a TEM image of the MOF precursor grown in situ on nickel foam in Comparative Example 1 of the present invention; Figure 8 This is a TEM image of the in-situ growth of a cerium-doped MOF precursor on nickel foam in Example 2 of the present invention; Fig. 9 TEM image of the cobalt tetraoxide catalyst in Comparative Example 1 of the present invention; Fig.10 This is a TEM image of the doped nano-oxide material in Example 2 of the present invention; Fig.11 Schematic diagram of underwater oxygen contact angle of doped nano-oxide material in Example 2 of the present invention; Fig.12The linear sweep voltammetry curves of the oxygen production reaction of the doped nano-oxide material in Examples 1 to 3 of the present invention and the comparative example; Fig.13 This is a graph showing the test results of the chronopotentiometry of the doped nano-oxide material in Example 2 of the present invention. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0025] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, "multiple" and "several" mean two or more, unless otherwise clearly and specifically defined.
[0026] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the conditions under which this application can be implemented. Therefore, they have no substantive technical significance. Any structural modification, change in proportional relationship or adjustment of size should still fall within the scope of the technical content disclosed in this application without affecting the effects and purposes that can be achieved by this application.
[0027] In a first aspect of an embodiment of the present application, a doped nano-oxide material is provided. The structure of the doped nano-oxide material is that second metal oxide particles doped with a first metal are grown in the pores and surface of nickel foam, the first metal is selected from one or more of cerium, lanthanum, gadolinium, and erbium, and the second metal is selected from one or more of cobalt, nickel, and iron.
[0028] In the embodiment of the present application, the second metal is selected from the above transition metal compound because its oxide structure is diverse, environmentally friendly and low cost; however, the second metal oxide has limited application due to its low electronic conductivity and inherent catalytic activity. The embodiment of the present application uses the doping of the first metal to regulate the electronic structure of the second metal oxide, and uses nickel foam (abbreviated as NF) as a supporting material to enhance its conductivity.
[0029] The doped nano-oxide material of the embodiment of the present application has a structure in which nano-oxide particles are grown on the pores and surface of nickel foam, and the nano-oxide particles are second metal oxide particles doped with a first metal. The doped nano-oxide material uses transition metal oxides instead of commonly used noble metal oxides, which reduces the material cost; and the material has a lower overpotential, exhibits better catalytic performance for electrocatalytic oxygen production, and the catalytic process is stable and efficient.
[0030] The preferred solution is that the first metal is cerium, the second metal is cobalt, and the oxide of the second metal is cobalt tetroxide. That is, the doped nano-oxide material is cerium-doped cobalt tetroxide-nickel foam nano-material, which can be expressed as Ce-Co3O4-NF.
[0031] In some embodiments, the structure of the doped nano-oxide material is a two-dimensional mesh structure. The doped nano-oxide material of the embodiment of the present application has a super-gas-repellent nano-mesh structure. The above-mentioned porous structure increases the specific surface area of the material, which is conducive to the electrocatalytic reaction. Specifically, the pore size of the doped nano-oxide material is 10nm to 100nm, and the specific surface area is 50m 2 / g~150m 2 / g.
[0032] The second aspect of an embodiment of the present application provides a method for preparing the above-mentioned doped nano-oxide material, comprising the following steps: dissolving a precursor of a first metal and a precursor of a second metal in a first solvent to obtain a first solution; dissolving an organic ligand in a second solvent, and adding an alkaline solution to obtain a second solution; mixing the first solution with the second solution, and adding nickel foam to obtain a third solution; subjecting the third solution to a hydrothermal reaction, and separating to obtain a solid-phase precursor; and calcining the solid-phase precursor to obtain the doped nano-oxide material.
[0033] In the preparation method of the embodiment of the present application, during the hydrothermal reaction, the precursor of the second metal and the organic ligand form a MOF material, the first metal is doped in the MOF material and grown in situ on the nickel foam together; then the doped nano oxide material of the present application is obtained by firing. That is to say, the embodiment of the present application uses the doping of the first metal to regulate the electronic structure of the second metal oxide, forms the first metal-doped MOF material by hydrothermal reaction, and uses the nickel foam as a supporting material to enhance its conductivity; the morphology and structure are adjusted by pyrolysis, the structure of the MOF material collapses, and the first metal-second metal oxide-NF super-gas-repellent nano-mesh derived from the MOF material is prepared. During the firing process, the MOF material is decomposed, and the material is converted from a two-dimensional sheet structure to a two-dimensional mesh structure.
[0034] In some embodiments, the organic ligand is selected from one or more of terephthalic acid, trimellitic acid, and 4,4'-biphenyldicarboxylic acid. It is understandable that the alkali solution reacts with the above-mentioned organic ligand to form a salt, which facilitates the organic ligand and the precursor of the second metal to form a MOF material. Specifically, the molar ratio of the organic ligand to the solute in the alkali solution is 1:1 to 5. In the embodiment of the present application, when the molar ratio of the organic ligand to the solute in the alkali solution is 1:2.5, the catalytic performance of the doped nano oxide material finally obtained is the best.
[0035] In some embodiments, the molar ratio of the first metal to the second metal in the first solution is 1:20 to 100. In the embodiments of the present application, the molar ratio of the first metal to the second metal determines the doping amount of the first metal in the second metal. For Ce-Co3O4-NF materials, in the case of less cerium doping, the oxygen production properties of the catalyst are slightly improved, but the effect is not obvious. When the doping ratio is appropriate, the element cerium significantly improves its catalytic effect by regulating the electronic structure of the active site cobalt. As the doping ratio increases further, part of the active site cobalt is covered by cerium, resulting in a decrease in the overall catalytic effect of the catalyst.
[0036] In some embodiments, the ratio of the total weight of the first metal and the second metal to the weight of the nickel foam is 1-2:1.
[0037] In some embodiments, the ratio of the total weight of the first metal and the second metal to the weight of the organic ligand is 1:1.
[0038] In some embodiments, the precursor of the first metal is selected from one or more of the nitrate, chloride, and sulfate of the first metal. The precursor of the second metal is selected from one or more of the nitrate, chloride, and sulfate of the second metal.
[0039] In some embodiments, the first solvent is selected from one or more of N,N-dimethylformamide and water. The second solvent is selected from one or more of N,N-dimethylformamide and water.
[0040] In some embodiments, the temperature of the hydrothermal reaction is 90°C to 110°C, and the time is 14h to 16h. In the embodiments of the present application, the precursor of the second metal and the organic ligand in the hydrothermal reaction form a MOF material, the first metal is doped in the MOF material and grown in situ on the nickel foam together, and the temperature of these reactions needs to be controlled within the above range. If the temperature is too low, the hydrothermal reaction cannot grow the corresponding MOF material on the nickel foam; if the temperature is too high, the morphology of the generated MOF material will be affected, and a two-dimensional sheet MOF material cannot be generated.
[0041] In some embodiments, the firing temperature is 390°C to 410°C, the heating rate is 1°C / min to 3°C / min, and the firing time is 5h to 7h. In the embodiments of the present application, the MOF material decomposes during the firing process, which needs to be completed within the above temperature range. The heating rate can ensure that the MOF material decomposes slowly so that the structure of the material does not change too much in a short period of time, so as not to destroy the porous network structure.
[0042] The third aspect of the embodiments of the present application provides the use of the above-mentioned doped nano-oxide material in electrolysis of water. The doped nano-oxide material of the embodiments of the present application is a super-aerophobic nano-net structure, has a lower overpotential, exhibits better catalytic performance, and is stable and efficient in the electrocatalytic process.
[0043] The specific implementation of the present application is further described below in conjunction with specific embodiments, but the implementation and protection of the present application are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.
[0044] Example 1 Doped nano-oxide material, the structure is that cerium-doped cobalt tetroxide particles grow in the pores and surface of nickel foam, forming a two-dimensional network structure. The specific surface area is 85.09m 2 / g.
[0045] The method for preparing the above-mentioned doped nano-oxide material comprises the following steps: (1) Add Co(NO3)2·6H2O (0.29 g) and Ce(NO3)3·6H2O (0.0043 g) to 5.0 mL N,N-dimethylformamide and disperse them evenly to obtain a first solution. Add NaOH (0.016 g) to 1.0 mL water and disperse them evenly to obtain an alkaline solution. Dissolve terephthalic acid (0.15 g) in 7 mL N,N-dimethylformamide, disperse them evenly, and add an alkaline solution to obtain a second solution. Add the second solution to the first solution, stir evenly, and add a nickel foam substrate to obtain a third solution. Add the third solution to a reactor and perform a hydrothermal reaction at 100°C for 15 h.
[0046] (2) After the third solution in step (1) reacts, the nickel foam is taken out, washed, dried, and dried at 60°C for 12 h. The foam is then heated to 400°C in an air atmosphere for sintering. The sintering time is 6 h, the heating rate is 2°C / min, and the foam is naturally cooled to room temperature to obtain a doped nano-oxide material.
[0047] The doped nano-oxide material of this embodiment has an oxygen production reaction of 100 mA·cm-2 At a current density of , the overpotential is about 331 mV.
[0048] Example 2 Doped nano-oxide material, the structure is that cerium-doped cobalt tetroxide particles grow in the pores and surface of nickel foam, forming a two-dimensional network structure. The specific surface area is 109.25m 2 / g.
[0049] The method for preparing the above-mentioned doped nano-oxide material comprises the following steps: (1) Add Co(NO3)2·6H2O (0.28 g) and Ce(NO3)3·6H2O (0.014 g) to 5.0 mL N,N-dimethylformamide and disperse them evenly to obtain a first solution. Add NaOH (0.016 g) to 1.0 mL water and disperse them evenly to obtain an alkaline solution. Dissolve terephthalic acid (0.15 g) in 7 mL N,N-dimethylformamide, disperse them evenly, and add the alkaline solution to obtain a second solution. Add the second solution to the first solution, stir evenly, and add the nickel foam substrate to obtain a third solution. Add the third solution to a reactor and perform a hydrothermal reaction at 90°C for 15 h.
[0050] (2) After the third solution in step (1) reacts, the nickel foam is taken out, washed, dried, and dried at 60°C for 12 h. The foam is then heated to 410°C in an air atmosphere for sintering. The sintering time is 6 h, the heating rate is 2°C / min, and the foam is naturally cooled to room temperature to obtain a doped nano-oxide material.
[0051] The doped nano-oxide material of this embodiment has an oxygen production reaction of 100 mA·cm -2 At a current density of , the overpotential is about 286 mV.
[0052] Example 3 Doped nano-oxide material, the structure is that cerium-doped cobalt tetroxide particles grow in the pores and surface of nickel foam, forming a two-dimensional network structure. The specific surface area is 87.99m 2 / g.
[0053] The method for preparing the above-mentioned doped nano-oxide material comprises the following steps: (1) Add Co(NO3)2·6H2O (0.28 g) and Ce(NO3)3·6H2O (0.022 g) to 5.0 mL N,N-dimethylformamide and disperse them evenly to obtain a first solution. Add NaOH (0.016 g) to 1.0 mL water and disperse them evenly to obtain an alkaline solution. Dissolve terephthalic acid (0.15 g) in 7 mL N,N-dimethylformamide, disperse them evenly, and add an alkaline solution to obtain a second solution. Add the second solution to the first solution, stir evenly, and add a nickel foam substrate to obtain a third solution. Add the third solution to a reactor and perform a hydrothermal reaction at 110°C for 15 h.
[0054] (2) After the third solution in step (1) reacts, the nickel foam is taken out, washed, dried, and dried at 60°C for 12 h. The nickel foam is then heated to 390°C in an air atmosphere for sintering. The sintering time is 6 h, the heating rate is 2°C / min, and the nickel foam is naturally cooled to room temperature to obtain a doped nano-oxide material.
[0055] The doped nano-oxide material in this embodiment has an oxygen production reaction of 100 mA·cm -2 At a current density of , the overpotential is about 311 mV.
[0056] Comparative Example 1 The preparation method of the cobalt trioxide catalyst comprises the following steps: (1) Add Co(NO3)2·6H2O (0.29 g) into 5.0 mL of N,N-dimethylformamide and disperse evenly to obtain a mixed solution 1; add NaOH (0.016 g) into 1.0 mL of water and disperse evenly to obtain an alkaline solution; dissolve terephthalic acid (0.15 g) in 7 mL of N,N-dimethylformamide, disperse evenly, and add the alkaline solution to obtain a ligand solution 2; add the ligand solution 2 into the mixed solution 1, stir evenly, and add the nickel foam substrate to obtain a mixed solution 3; add the mixed solution 3 into a reactor and carry out a hydrothermal reaction at 100 °C for 15 h.
[0057] (2) After the reaction of the mixed solution 3 in step (1), the nickel foam is taken out, washed, dried, and dried at 60°C for 12 hours. The mixture is then heated to 400°C in an air atmosphere for sintering. The sintering time is 6 hours, the heating rate is 2°C / min, and the mixture is naturally cooled to room temperature to obtain the cobalt tetroxide catalyst.
[0058] The cobalt tetraoxide catalyst of this comparative example was 100 mA·cm -2 At a current density of , the overpotential is about 336 mV.
[0059] The doped nano-oxide materials of Examples 1 to 3 and the catalyst of Comparative Example 1 were characterized respectively, and the results are as follows. Figure 1 It can be seen that the MOF precursors in Examples 1 to 3 and Comparative Example 1 were successfully prepared. Figure 2 It can be seen that the main components of the doped nano-oxide materials of Examples 1 to 3 and the catalyst of Comparative Example 1 are all cobalt tetraoxide. Figures 3 to 6 It can be seen that the doping of rare earth element cerium does not change the original morphology of the MOF precursor, which is still a two-dimensional lamellar structure.
[0060] from Figures 7 to 10 It can be seen that after firing in air, the original two-dimensional sheet structure is transformed into a two-dimensional network structure. This porous network structure increases the specific surface area of the material, which is conducive to the electrocatalytic reaction. Fig.11 It can be seen that the doped nano-oxide material of Example 2 has a super-aerophobic surface property.
[0061] At room temperature, in a 1.0 mol / L potassium hydroxide solution, the doped nano-oxide materials of Examples 1 to 3 and the cobalt tetroxide catalyst of Comparative Example 1 were clamped with an electrode clamp and used as working electrodes to perform electrochemical tests. The tests were all performed using CHI 760E (manufactured by Shanghai Chenhua Instrument Co., Ltd.).
[0062] 1. Linear sweep voltammetry (LSV) test: Oxygen production test results Fig.12 After the three-electrode system was connected, 30 cycles of cyclic voltammetry (CV) were performed to activate the catalyst. The OER properties of the sample were then measured using linear voltammetry (LSV) with a scan rate of 5 mV·s -1 , the scanning range was from 1.0 V to 1.8 V vs RHE.
[0063] The potential in this work was converted to the reversible hydrogen electrode (RHE) potential according to the Nernst equation (ERHE = EAg / AgCl + 0.059pH + 0.21). The overvoltage (η) of the oxygen production reaction was calculated according to the following formula: η(V) = ERHE.
[0064] The linear sweep voltammetric curves of the oxygen production reaction of Ce-Co3O4-NF materials with different doping ratios were tested under the same conditions. The results are as follows Fig.12As shown. It can be seen that the nano oxide materials prepared after doping with cerium in Examples 1 to 3 all have good electrocatalytic oxygen production performance, and different cerium doping ratios will affect their properties. In the case of less cerium doping, the oxygen production properties of the catalyst are slightly improved, but the effect is not obvious. When the doping ratio is appropriate, elemental cerium significantly improves its catalytic effect by regulating the electronic structure of the active site cobalt. As the doping ratio increases further, part of the active site cobalt is covered by cerium, resulting in a decrease in the overall catalytic effect of the catalyst. The doped nano oxide material of Example 2 has the best electrocatalytic water decomposition and oxygen production performance.
[0065] 2. Chronopotentiometry to test the stability of doped nano-oxide materials The results of the chronopotentiometry test are as follows Fig.13 As shown. For the oxygen production reaction, at a current density of 100 mA cm -2 Under the condition of 100 hours, the stability of the cerium-doped nano-oxide material (i.e., the nano-oxide material of Example 2) with the best electrocatalytic decomposition of water and oxygen production performance was tested by chronopotentiometry. The results showed that the performance of the material remained stable within 100 hours, and the voltage did not increase significantly, indicating that the cerium-doped cobalt tetroxide material can maintain a stable OER catalytic effect under high current conditions. The nano-oxide materials prepared in other embodiments can also maintain a stable OER catalytic effect under high current conditions, which can be referred to Fig.13 shown.
[0066] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A doped nano-oxide material, characterized in that: The structure of the doped nano-oxide material is that second metal oxide particles doped with a first metal are grown in the pores and surface of nickel foam, the first metal is selected from one or more of cerium, lanthanum, gadolinium, and erbium, and the second metal is selected from one or more of cobalt, nickel, and iron.
2. The doped nano-oxide material according to claim 1, characterized in that: The structure of the doped nano-oxide material is a two-dimensional network structure.
3. The doped nano-oxide material according to claim 1, characterized in that: The first metal is cerium, the second metal is cobalt, and the oxide of the second metal is tricobalt tetroxide.
4. The doped nano-oxide material according to any one of claims 1 to 3, characterized in that: The pore size of the doped nano-oxide material is 10nm to 100nm, and the specific surface area is 50m 2 / g~150m 2 / g.
5. The method for preparing the doped nano-oxide material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Dissolving a precursor of a first metal and a precursor of a second metal in a first solvent to obtain a first solution; dissolving the organic ligand in a second solvent, and adding an alkali solution to obtain a second solution; The first solution and the second solution are mixed, and nickel foam is added to obtain a third solution; After subjecting the third solution to a hydrothermal reaction, a solid phase precursor is obtained by separation; The doped nano-oxide material is obtained by firing the solid-phase precursor.
6. The method for preparing the doped nano-oxide material according to claim 5, characterized in that: The organic ligand is selected from one or more of terephthalic acid, trimellitic acid, and 4,4'-biphenyldicarboxylic acid.
7. The method for preparing doped nano-oxide material according to claim 5, characterized in that: The molar ratio of the first metal to the second metal in the first solution is 1:20-100; and / or, The molar ratio of the organic ligand to the solute in the alkali solution is 1:1-5.
8. The method for preparing doped nano-oxide material according to claim 5, characterized in that: The ratio of the total weight of the first metal and the second metal to the weight of the nickel foam is 1-2:1; and / or, The ratio of the total weight of the first metal and the second metal to the weight of the organic ligand is 1:
1.
9. The method for preparing a doped nano-oxide material according to any one of claims 5 to 8, characterized in that: The precursor of the first metal is selected from one or more of the nitrate, chloride and sulfate of the first metal; the precursor of the second metal is selected from one or more of the nitrate, chloride and sulfate of the second metal.
10. The method for preparing a doped nano-oxide material according to any one of claims 5 to 8, characterized in that: The first solvent is selected from one or more of N,N-dimethylformamide and water; and / or the second solvent is selected from one or more of N,N-dimethylformamide and water.
11. The method for preparing a doped nano-oxide material according to any one of claims 5 to 8, characterized in that: The temperature of the hydrothermal reaction is 90°C to 110°C, and the time is 14h to 16h; and / or the firing temperature is 390°C to 410°C, the heating rate is 1°C / min to 3°C / min, and the firing time is 5h to 7h.
12. Use of the doped nano-oxide material according to any one of claims 1 to 4 or the doped nano-oxide material prepared by the preparation method according to any one of claims 5 to 11 in electrolyzed water.